2016
DOI: 10.5007/1980-0037.2016v18n6p621
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity during official soccer matches

Abstract: -The aims of the study were: 1) to analyze the exercise intensity in several phases (six phases of 15 min) of soccer matches; 2) to compare the match time spent above anaerobic threshold (AT) between different age groups (U-17 and U-20); and 3) to compare the match time spent above AT between players' positions (backs, midfielders, forwards and wingabcks). Forty-four male soccer players were analyzed. To express players' effort, the heart rate (HR) was continuously monitored in 29 official matches. Further, HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Although the reserve balls were prepared around the playing field, when the game started again, the players couldn´t keep the HR values at a high level. Coelho et al (2016) found that the players spent a statistically significant more time above the ANT level in the first half of the match than in the second half. By using small forms of the SSG games, it is possible for us to prepare the players for the load at such level.…”
Section: Discussionmentioning
confidence: 83%
“…Although the reserve balls were prepared around the playing field, when the game started again, the players couldn´t keep the HR values at a high level. Coelho et al (2016) found that the players spent a statistically significant more time above the ANT level in the first half of the match than in the second half. By using small forms of the SSG games, it is possible for us to prepare the players for the load at such level.…”
Section: Discussionmentioning
confidence: 83%
“…After screening the title, abstract and full text, a total of 24 studies were included in this systematic review (Figure 1). A description of the 24 included articles is presented in Table I (Al‐Jaser & Hasan, 2006; Aragón‐Vargas, Moncada‐Jiménez, Hernández‐Elizondo, Barrenechea, & Monge‐Alvarado, 2009; Castro‐Sepulveda et al, 2015; Castro‐Sepulveda, Astudillo, Letelier, & Zbinden‐Foncea, 2016; Chapelle et al, 2017; Coelho et al, 2012; Da Silva et al, 2012; Diaw et al, 2014; Duffield, Mccall, Coutts, & Peiffer, 2012; Gibson, Stuart‐Hill, Pethick, & Gaul, 2012; Gordon, Kassier, & Biggs, 2015; Guttierres, Natali, Vianna, Reis, & Marins, 2011; Harvey, Meir, Brooks, & Holloway, 2008; Kilding et al, 2009; Kurdak et al, 2010; Magee, Gallagher, & Mccormack, 2017; Mattausch et al, 2017; Maughan, Merson, Broad, & Shirreffs, 2004; Maughan, Shirreffs, Merson, & Horswill, 2005; Maughan, Watson, Evans, Broad, & Shirreffs, 2007; Philips, Sykes, & Gibson, 2014; Silva et al, 2011; Van Biervliet et al, 2013; Williams & Blackwell, 2012). The Cohen's kappa between the two researchers was 0.93 for the independent systematic search and 1.00 for data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the hydration status, 17 studies used USG (Al‐Jaser & Hasan, 2006; Aragón‐Vargas et al, 2009; Castro‐Sepulveda et al, 2015; Castro‐Sepulveda, Astudillo et al, 2016; Chapelle et al, 2017; Da Silva et al, 2012; Diaw et al, 2014; Duffield et al, 2012; Gibson et al, 2012; Gordon et al, 2015; Guttierres et al, 2011; Kilding et al, 2009; Kurdak et al, 2010; Magee et al, 2017; Mattausch et al, 2017; Philips et al, 2014; Silva et al, 2011), 3 studies used U Osm (Maughan et al, 2004, 2005, 2007), 2 studies used a combination of USG and U Osm (Coelho et al, 2012; Van Biervliet et al, 2013), 1 study used a combination of USG and U Col (Harvey et al, 2008), and 1 study used a combination of U Osm and U Col (Williams & Blackwell, 2012). A total of 19 studies assessed male soccer players (Al‐Jaser & Hasan, 2006; Aragón‐Vargas et al, 2009; Castro‐Sepulveda et al, 2015; Coelho et al, 2012; Da Silva et al, 2012; Diaw et al, 2014; Duffield et al, 2012; Gordon et al, 2015; Guttierres et al, 2011; Harvey et al, 2008; Kurdak et al, 2010; Magee et al, 2017; Maughan et al, 2004; Maughan et al, 2005; Maughan et al, 2007; Philips et al, 2014; Silva et al, 2011; Van Biervliet et al, 2013; Williams & Blackwell, 2012) whereas 5 studies examined female soccer players (Castro‐Sepulveda et al, 2015; Chapelle et al, 2017; Gibson et al, 2012; Kilding et al, 2009; Mattausch et al, 2017). Professional level soccer players were analysed in 19 studies (Al‐Jaser & Hasan,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mental condition at the end of exercises can be common in several modalities with similar physiological demands and intensity 28,29 midfielders, forwards and wingabcks. A possible explanation for these results can be supported by the theory of the central governor 30 by which fatigue is caused, mainly in aerobic exercises, being signaled by the brain acting to preserve the body's cellular homeostasis 31,32 .…”
Section: Discussionmentioning
confidence: 96%